CHRONIC TRACHOMA: COMPARISON OF AZITHROMYCIN VERSUS TOPICAL TETRACYCLINE IN RURAL SINDH POPULATION: Azithromycin Versus Topical Tetracycline in Trachoma - Sheikh, Muhammad Muneeb (Pakistan Armed Forces Medical Journal, 2016)
Objective: To compare the efficacy of oral azithromycin with topical tetracycline for treating chronic trachoma in rural Sindh population of Pakistan. Study Design: Randomized Control Trial (RCT). Place and Duration of Study: CMH Pano Aqil from October 2010 to September 2013. Material and Methods: A total of 214 individuals with active trachoma in at least one eye were recruited in the study and randomly assigned to either treatment group. Patients visited after 10 weeks. The outcome was ‘resolved disease’.The data was analyzed using SPSS 20. Results: Patients in azithromycin group were significantly more likely to have resolved disease as compared to tetracycline group at 10 weeks of follow up(86% vs 71%; 95% confidence interval CI, 0.28-0.87; p=0.015). Differences within the age groups were not significant (children, p=0.072; elderly, p=0.091). Conclusion: Single dose oral azithromycin was significantly more likely to achieve better outcome in chronic trachoma in rural population where compliance had been an issue.